2009
DOI: 10.2459/jcm.0b013e32832997f3
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia and reperfusion-induced arrhythmias: role of hyperoxic preconditioning

Abstract: f Background Hyperoxic preconditioning is known to protect the heart against necrosis and contractile dysfunction, but protection against arrhythmias has not been well characterized.Objective The authors hypothesized that pre-exposure to normobaric hyperoxia (H) reduces ischemia and reperfusion-induced arrhythmias in isolated rat hearts.Methods Following 60 and 180 min of hyperoxia treatment, rat hearts were isolated immediately (H60 and H180) or 24 h afterward (H60/24 and H180/24), and subjected to 30 min of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Furthermore, IPC measurably decreased ventricular arrhythmia during the initial period of reperfusion, though no significant difference in incidence and scores of ventricular arrhythmia between the control and IPC groups was achieved because of the small sample size. These results correspond with the findings of previous studies in rats with myocardial IRI in vivo [18][19][20]. The results of the present study also showed that IPOC produced a significant inhibitory effect on ventricular arrhythmia during the initial period of reperfusion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, IPC measurably decreased ventricular arrhythmia during the initial period of reperfusion, though no significant difference in incidence and scores of ventricular arrhythmia between the control and IPC groups was achieved because of the small sample size. These results correspond with the findings of previous studies in rats with myocardial IRI in vivo [18][19][20]. The results of the present study also showed that IPOC produced a significant inhibitory effect on ventricular arrhythmia during the initial period of reperfusion.…”
Section: Discussionsupporting
confidence: 82%
“…The severity of arrhythmias was quantified by a scoring system, where hearts without arrhythmias were given a score of 0, premature ventricular beats (PVB) only a score of 1, bigeminy/salvos a score of 2, VT a score of 3, frequent VT or transient VF a score of 4, and a score of 5 was given to the hearts with frequent or sustained VF or death of the rat. The number corresponded to the most severe type of arrhythmia observed in each heart, and scores were used for intergroup analysis of their severity [17,18].…”
Section: Arrhythmias Scoresmentioning
confidence: 99%
“…Animal studies suggest that hyperoxia has favourable effects on myocardial ischaemic injury through a preconditioning effect on cardiac muscle . A similar study in humans, exposing patients to hyperoxia (F I O 2 > 0.96) for 130 and 60 min before coronary artery bypass grafting, had no effect on the cardiac enzymes creatine kinase MB (CK‐MB) and troponin I .…”
Section: Methodsmentioning
confidence: 97%
“…Since ROS is considered to be one of the main factors triggering the mechanism of death in ischemic/reperfusion myocardial damage, the prevention of the synthesis of ROSs or their neutralization is obviously crucial for the survival or recovery of cardiomyocyte function (Pourkhalili et al 2009). The pharmacological group used for this purpose is antioxidants.…”
Section: Resultsmentioning
confidence: 99%